(3SeJ GdbHdIs - (3GHf GdgjKe , eMeO Hf GdMSf Hf GdgjKe, CHh Ydj HWdjehS GdKGfj,J (B430 (3g` s
(3ChdgG (B:s
(3bGd QMeI Gdd SeJ GdbHdI gh GdLgI GdJi GPG bGHdgG GdGfSGf cGf cGdfGXQ Edi bWQ GdYGde s
(3BNQgG (B:s
(3aMjK GfJgJ ChUdfG Hjfg hHjf eQcR GdOGFQI HNW eSJbje hgh GdSeJ GdeWdhH JeJ s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B83 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B225s
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi s
Keywords: (3Gdadcs